Method of Payments in the Merger and Acquisitions Transaction: The Case of Saudi Arabia - Zakaria, Nadisah; Kamaludin, Kamilah; Alkhalifa, Alya (Journal of Reviews on Global Economics, 2019)
The performance of mergers and acquisitions companies has been broadly investigated in diverse advanced share markets primarily in the US and UK economies. However, little evidence has been found in an emerging market like Saudi Arabia. For this reason, this study examines the long-run share performance of acquirer' companies listed on the Saudi Arabia Stock Exchange (Tadawul) from 1st January 2000 to 31st August 2017. Using the buy-and-hold abnormal return method, the present study finds that the acquirer companies' shares for the cash payment method continues to outperform their counterparts of non-cash payment against the equal-weighted and value-weighted indexes. The presence of abnormal return opportunities that may be exploited by investors in the three-year holding period following the completion of M&A events might provide valuable insight to individual and institutional investors. As there is no national evidence on share performances of acquirer's companies over the long-run period, the present findings add to a growing body of M&A literature.